CHILDHOOD CONSTIPATION - A NEW EPIDEMIC: Childhood Constipation - A New Epidemic - Safdar, Lt Col C. Aqeel (Pakistan Armed Forces Medical Journal, 2010)
In third world countries diarrhea has always been the main focus of care- givers for children. However a fair number of constipated children are also referred to us mainly to rule out pathological constipation, especially the possibility of Hirschsprung’s disease. Of the many disorders afflicting children, severe or perceived constipation, often has the most disruptive effect on the family. The parents often are upset out of all proportion to the degree of the child’s illness. They often are referred because their doctor is at his wits end and needs help. Frequently, these children arrive with a stack of X-Rays, reported as megacolon, with demand of a rectal biopsy ‘to rule out Hirschsprung’s disease’. However, a careful history sometimes is all that is required without resorting to further tests.